ENSINO SUPERIOR À ORDEM DO CAPITAL INTERNACIONAL - Vanessa Maria de Oliveira Borges; Edson Tomaz de Aquino (Revista Gestão Universitária na América Latina, 2013)
The arranging and the reordering of power in today's world do not exclude the university organization. The political, economic, social and cultural surroundings exerts a huge impact on higher education, which can not and should not stay out of the changes that arise in today’s society. That is why international cooperation has been deployed as a process of great relevance in the university world, being the point of academic discussion in several countries. Moreover, the reduction of the states interference in their economies plus the internationalization of services, make the higher education be treated as a commodity in the international market. In this context, this study aims to examine the elements of the central political debate about the demands of the international capital in Brazilian higher education. To facilitate the achievement of the goals of this research - among them, analyze the offensive action of international capital in Brazilian higher education - will be used as theoretical framework, the Globalist Paradigm of International Relations, from the perspective of the Dependency Theory and the center-periphery relations. The method of research used is qualified as explanatory (as to their goals) and as abstract subject (in nature). The procedures for data collection turned to obtaining secondary data, already published in books, articles, journals, websites etc. Thus, this work qualifies itself as bibliographic, with regard to its object, and qualitative with regard to its approach, realizing thus an interpretive analysis of the data obtained and the observed phenomena.